Implementation of adaptive PID control for maintaining temperature stability during steady-state conditions in stirred heating tank - Valentina, Pricylia; Tjahjono, Hendro; Pamitran, Agus Sunjarianto; Roswandi, Iwan; Setiawan, Putut Hery; Budiman, Arif Adtyas; Haryanto, Dedy; Sanda, Sanda; Prayogo, Kukuh; Juarsa, Mulya (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Temperature stability is a crucial factor in industries such as chemicals, pharmaceuticals, and food processing, where fluctuations can damage product quality and increase energy consumption. This study aims to optimize heater power control using an adaptive proportional integral derivative (PID) control system to maintain temperature stability under steady-state conditions. The method involves applying adaptive PID control to a stirred heating tank using LabVIEW software with a national instruments controller module and a single-phase SCR to regulate heater power and adjust control parameters in real time. The results indicate that the system operates more effectively under stable conditions, with faster response times and a lower overshoot of less than 0.12%. However, under disturbed conditions, such as water drainage and replacement, the system requires more time to adjust the temperature and experiences increased energy consumption and heat loss. Despite this, the system still achieves an energy efficiency improvement, with efficiency values ranging from 77.66% to 80.03%. The implementation of adaptive PID control demonstrates significant potential in enhancing system accuracy and response to temperature changes, contributing to the development of more efficient industrial control technologies.